1995
DOI: 10.1212/wnl.45.8.1483
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lacunar infarction syndromes

Abstract: Patients with hypertension or diabetes, and those who currently smoke, are at a higher risk of lacunar stroke, whereas those who undertake regular physical exercise may be at lower risk. The high risk associated with hypertension but absent risk with heart disease supports the "lacunar hypothesis" of a unique pathophysiologic mechanism for lacunar stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 23 publications
9
65
0
1
Order By: Relevance
“…15 Hypertension, diabetes, hypercholesterolemia, and current smoking were significantly more prevalent in northern Manhattan Hispanics and blacks than in whites. Lacunar stroke is associated with hypertension, diabetes, and smoking 13,24 ; extracranial atherosclerotic stroke is associated with male gender and smoking 25 ; and NOMAS has previously reported a relationship between hypercholesterolemia and diabetes and intracranial atherosclerotic stroke. 10 Consequently, the incidence of lacunar and intracranial and extracranial atherosclerotic stroke was higher in northern Manhattan black and Hispanic subjects than in whites.…”
Section: Discussionmentioning
confidence: 99%
“…15 Hypertension, diabetes, hypercholesterolemia, and current smoking were significantly more prevalent in northern Manhattan Hispanics and blacks than in whites. Lacunar stroke is associated with hypertension, diabetes, and smoking 13,24 ; extracranial atherosclerotic stroke is associated with male gender and smoking 25 ; and NOMAS has previously reported a relationship between hypercholesterolemia and diabetes and intracranial atherosclerotic stroke. 10 Consequently, the incidence of lacunar and intracranial and extracranial atherosclerotic stroke was higher in northern Manhattan black and Hispanic subjects than in whites.…”
Section: Discussionmentioning
confidence: 99%
“…
ypertension is the most important risk factor for lacunar infarcts [1][2][3][4][5][6] and although abdominal visceral fat accumulation is thought to be associated with cardiovascular risk factors such as hypertension, its relationship with lacunar infarcts has not been investigated in Japanese men. 7 Abdominal visceral fat accumulation is associated with diet, lack of physical activity, drinking alcohol, mental stress, and the aging process.
…”
mentioning
confidence: 99%
“…Cigarette smoking has been well-documented as a risk factor for ischemic stroke in general, with relative risks of 1.5 -5.7 [5]. It is also well-reported that smoking degrades carotid IMT [6], a well-known surrogate marker for atherosclerosis [7].…”
Section: Introductionmentioning
confidence: 99%